Status of Sustainability Management of The Mangrove Ecosystem in Mangrove Hijau Daun Area of Bawean Island Gresik District (Agrikan Jurnal Agribisnis Perikanan, 2024)
Mangroves are an ecosystem that has an important function for coastal areas, the existence of mangroves provides ecological, economic, and social functions. Therefore, mangrove ecosystem management must be carried out using an environmental sustainability approach and natural resource sustainability to avoid damage to the existence of the mangrove ecosystem. This research aims to analyze the status of sustainability of mangrove ecosystem management in the Mangrove Hijau Daun area, Daun Village, Sangkapura District, Bawan Island, Gresik Regency. This research was carried out from June to August 2023. The method used was RAPFISH (Rapid Appraisal for Fisheries) analysis with a Multidimensional Scaling (MDS) approach based on ecological, economic, social, and institutional dimensions. The results of the research show that the sustainability status of the mangrove ecosystem in the green leaf mangrove area of Bawean Island obtained a multidimensional index value of 72.56, including in the quite sustainable category, each dimension has an index value, namely the ecological dimension of 88.68, the economic dimension of 49.80. , the social dimension is 78.40, and the institutional dimension is 88.12. The economic dimension is a dimension whose management needs to be encouraged because it has an index value in the less sustainable category.
Keywords: Mangrove Ecosystem; Sustainable Management; Bawean Island